Parametric optimization of wear parameters of hybrid composites (LM6/B4C/fly ash) using Taguchi technique - Udaya Prakash, Jayavelu; Ananth, Subramani; Jebarose Juliyana, Sunder; Cep, Robert; Khedkar, Nitin; Salunkhe, Sachin; Abouel Nasr, Emad; Kamrani, Ali (Frontiers in Mechanical Engineering, 2023)
Wear is prominent in sliding components, so tribology property plays a major role in automotive as well as in the aerospace industries. In this work, Aluminium alloy LM6/B4C/Fly Ash hybrid composites with three different weight percentages of reinforcement were fabricated using the low-cost stir casting technique, and the experiments were conducted based on the Design of Experiments (DoE) approach and optimized using Taguchi's Signal to noise ratio (S/N) analysis. The analysis was conducted with process parameters like Sliding Speed (S), Sliding distance (D), load (L) and reinforcement percentage (R %), the responses are Coefficient of Friction (COF) and Specific wear rate (SWR). Aluminum alloy reinforced with 9 wt% hybrid (LM6 + 4.5% B4C + 4.5% Fly Ash) has a low density and high hardness compared with other composites and base alloys. The optimum parameters for obtaining minimum SWR are S -1 m/s, D -500 m, L -45 N, and R% -6 wt% Hybrid (3% Fly ash and 3% boron carbide). The optimum parameters for obtaining minimum COF are S -1.5 m/s, D -500 m, L -30 N, and R% -9 wt% Hybrid (4.5% Fly ash and 4.5% boron carbide). Load (28.34%) is the most significant parameter for obtaining minimum SWR, and DL (31.62%) for obtaining minimum COF. SEM images of the worn pins show the various wear mechanisms of the AMCs. The hybrid composite produced is new and these may be used for piston liner and brake pad applications.